Protest politics and the democratization of South Korea : strategies and roles of women - Shin, Youngtae (Lexington Books, 2014)
This book examines the role of women involved in South Korea's democratization movement. Through its study of older women and the gender roles and values of Korean society manifested in the "Mothers" movement, this book challenges social movement theories that focus on those on the front line but ignore those behind the scenes.